2017
DOI: 10.1016/j.foodres.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Sweet cherries from Fundão possess antidiabetic potential and protect human erythrocytes against oxidative damage

Abstract: Cherries are one of the most appreciated summer fruits due to their attractive colour, sweet taste, high water content, low level of calories and composition in bioactive compounds which, in turn, are important to prevent some pathologies like diabetes, cardiovascular diseases and cancer. In this work we evaluated the phenolic profile and biological potential of 5 varieties of sweet cherries from Fundão region (Portugal) (Saco, Sweetheart, Satin, Maring and Hedelfinger). A total of 23 phenolic compounds were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(134 citation statements)
references
References 36 publications
19
105
0
1
Order By: Relevance
“…μg GAE/mL) with major activity of pulps extracts (1 and 0.7 μg GAE/mL, before and after GD digestion). The activity was much higher than extracts of other fruits known for its capacity for the prevention of oxidation and cellular damage, such as quince (Cydonia oblonga) or sweet cherries (Prunus avium) (500 μg GAE/mL and 73 μg GAE/mL, respectively)(Magalhães et al, 2009;Gonçalves et al, 2017); and similar to orange chilto extracts (0.40-1.21 μg GAE/mL,Orqueda et al, 2017). All the extracts were good scavengers of reactive oxygen and nitrogen species (ROS/RNS), with IC 50 values between 4.2-78.3 μg GAE/mL.…”
mentioning
confidence: 89%
“…μg GAE/mL) with major activity of pulps extracts (1 and 0.7 μg GAE/mL, before and after GD digestion). The activity was much higher than extracts of other fruits known for its capacity for the prevention of oxidation and cellular damage, such as quince (Cydonia oblonga) or sweet cherries (Prunus avium) (500 μg GAE/mL and 73 μg GAE/mL, respectively)(Magalhães et al, 2009;Gonçalves et al, 2017); and similar to orange chilto extracts (0.40-1.21 μg GAE/mL,Orqueda et al, 2017). All the extracts were good scavengers of reactive oxygen and nitrogen species (ROS/RNS), with IC 50 values between 4.2-78.3 μg GAE/mL.…”
mentioning
confidence: 89%
“…2.5.2 HPLC-DAD analysis. Twenty microliters of each sample were analyzed on a LC model Agilent 1260 system (Agilent, Santa Clara, CA, USA) using a Nucleosil R 100-5 C18 column (25.0 cm × 0.46 cm; 5 µm particle size waters; Macherey-Nagel), according to Gonçalves, Bento, Silva, and Silva (2017). Detection was achieved with an Agilent 1260 Infinity DAD using the ChemStation software supplied by Agilent Technologies (Waldbronn, Germany).…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…It has been considered that CA contributes to alleviate oxidative stress in renal tissue of cadmium chloride in toxicated rats . In addition, Gonçalves et al . demonstrated that sweet cherries rich in flavonoids and phenolic acids, particularly p ‐coumaric acid, protect human erythrocytes from hemolysis.…”
Section: Resultsmentioning
confidence: 99%